Emotions and investments: the influence of investor sentiment on cryptocurrencies during the Covid-19 pandemic - Santos, Rayane Farias dos; Silva, César Augusto Tibúrcio (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2025)
Purpose: The study analyzed the relationship between investor sentiment and the return and trading volume of the main cryptocurrencies in Brazil during the COVID-19 pandemic. Methodology: Two metrics were used to capture investor sentiment: the Happiness Index (HFI) and the Fear Index (FEARS), collected through Twitter and Google tools. Data related to cryptocurrencies were collected from the Cryptocompare website. Quantile regressions were used to analyze variations in the impact of investor sentiment on different types of currencies. Results: The results indicated that happiness and fear affect cryptocurrencies heterogeneously, with HFI causing negative and positive impacts on the return of assets such as BTC, USDC, and USDT. FEARS had a predominantly negative impact on the return of cryptocurrencies such as BTC and BRZ but was positive on ETH. Regarding trading volume, IFH had an ambiguous influence on BRZ, while FEARS reduced the volume of BTC, USDT, and USDC. The distinct patterns of impact identified suggest that investor sentiment may be a key indicator for formulating strategies in a highly volatile and emotionally reactive market. Contributions of the Study: It contributes significantly to the literature by focusing on the Brazilian cryptocurrency market, which has been little explored in international research. It uses a quantile approach to examine how investor sentiment impacts multiple cryptocurrencies, offering a more detailed and non-linear analysis, something rare in the literature. Furthermore, investigating the behavior of cryptocurrencies in Brazil during COVID-19 provides critical insights into how collective emotions, such as fear and euphoria, affect market movements, especially in an environment dominated by individual investors, making the study relevant for emerging markets.